Pengaruh Kurikulum Merdeka Belajar Terhadap Motivasi Belajar SMA di Bantul - Chandra, Ahmad; Purwanta, Edi; Eliasa, Eva Imania; Shoihin, Nur; Syafitri, Deananda (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2025)
The background of this issue is Merdeka Learning Curriculum, a pedagogical initiative designed to increase learning flexibility and encourage active student engagement. The purpose of this study is to analyze the impact of Merdeka Curriculum on the learning motivation of high school students in Bantul. A quantitative approach was used, with a survey method to collect data from 130 students of SMA Negeri 2 Bantul consisting of grades X, XI, and XII. Respondents were proportionally selected from each level to represent the diversity of experiences in implementing Merdeka Curriculum. Data were collected through a Likert scale questionnaire. The findings of this study, as evidenced by simple linear regression analysis, show that Merdeka Curriculum has a substantial effect on learning motivation (B = 0.266; Sig. = 0.000). Elements of the Merdeka Curriculum such as freedom to choose subjects, formative assessment, and project-based learning contribute to increasing students' intrinsic motivation. In addition, the teacher's role as a facilitator was identified as an important factor in increasing student engagement. This finding is in line with the principles of Self-Determination Theory, which emphasizes the role of autonomy in increasing motivation. This research recommends optimizing the implementation of Merdeka Curriculum through increased support for teachers and educational institutions. Future research needs to explore the long-term impact of this curriculum on student achievement.